Analysis of the BOLD responses on EEGfMRI acquisition in patients with epilepsy - de Campos, Brunno M.; Coan, Ana C.; Beltramini, Guilherme C.; Covolan, Roberto J. M.; Cendes, Fernando (Revista Brasileira de Física Médica, 2015)
The technique of magnetic resonance imaging (MRI), characterized by high spatial resolution, associated with electroencephalography (EEG), characterized by high temporal resolution, can be a powerful tool to study neurological disorders, including epilepsy. Electroencephalography is a mechanism to record electrical brain activity, using principles of Electronics, Physics and Physiology. Functional MRI (fMRI) relies on the different magnetic properties of blood depending on its oxygen content. The goal of functional imaging is to obtain images that are sensitive to brain function. To this end, we aimed to understand the mechanisms of neural activity and the processes related to it. This paper describes the methodology of the combined EEG-fMRI method in a tertiary hospital, and assesses the results of 16 exams regarding their concordance with the clinical history and clinical applicability of the technique. The results of the exams were statistically analyzed with the software SPM8. BOLD (Blood Oxygenation Level Dependent) responses were analyzed considering the clinical history of each volunteer. The studies that showed statistically significant activation areas consistent with clinical history were considered compatible (seven exams) while the studies with results not consistent were considered incompatible (one exam). Six compatible exams were considered clinically relevant, because they add information regarding the definition of the epileptogenic zone or epileptic syndrome. The studies with absence of epileptiform activity on EEG (three exams) or significant BOLD activations (three exams) were considered null. Two exams were excluded due to excessive head motion. EEG-fMRI is a promising technique that can be important to improve the understanding of neurological disorders, including epilepsy. The method may be used in the future as an important diagnostic tool for refractory epileptic patients as it may add information about the localization of epileptogenic zone or definition of epileptic syndrome.